Une injustice épistémique aux conséquences institutionnelles : le cas des relations de sollicitude marginalisées - Lanthier, Alec Aubrey (Université du Québec à Montréal, 2023)
Ce mémoire théorise les relations de sollicitude, soit les relations entre deux adultes consentants qui se connaissent bien, qui maintiennent un contact direct prolongé et qui partagent une histoire commune. Ces relations permettent à chaque personne de communiquer ses besoins et désirs de manière à ce que l’autre personne ait accès aux connaissances intimes particulières lui permettant de faire la promotion de son bien-être. Elles comportent une dimension affective qui influence ce travail de sollicitude de façon à ce qu’il soit effectué de manière impliquée [solicitously], constante et enthousiaste (voir Brake, 2012, pp. 82, 85-86, 160). J’y défends la thèse selon laquelle certains types de relations de sollicitude sont marginalisés des institutions gouvernementales encadrant les relations romantiques, monogames et à long terme en raison de l’influence d’idéologies oppressives, et que cette marginalisation constitue une injustice sociale. Ces idéologies oppressives incluent le racisme, la xénophobie, la suprématie blanche, occidentale et judéochrétienne, le patriarcat, le sexisme, la cishétéronormativité, l’homophobie et la transphobie. Pour ce faire, j’introduis mon argument généralisé pour la reconnaissance institutionnelle des relations de sollicitude marginalisées. Suivant cet argument, toute relation 1) étant une relation de sollicitude et 2) ayant été marginalisée en raison de l’influence historique et actuelle d’idéologies oppressives est une relation de sollicitude marginalisée. Puisque cette marginalisation résulte de l’influence d’idéologies oppressives, il s’agit d’une injustice qui doit être corrigée afin de tendre vers la justice sociale. Afin de démontrer l’applicabilité de cet argument, j’introduis trois ensembles de cas, soit les relations LGBTQIA2S+ n’étant pas présentement reconnues dans certains ou dans tous les pays occidentaux, les relations non monogames et les relations amicales ou familiales ne faisant pas partie de la famille nucléaire conventionnelle. Au sein du premier chapitre, je démontre que ces relations correspondent au deuxième critère de mon argument généralisable, soit le fait d’avoir été marginalisées en raison de l’influence d’idéologies oppressives. Le deuxième chapitre permet de démontrer qu’ils correspondent également au premier critère, soit le fait d’être des relations de sollicitude. Pour ce faire, je démontre qu’elles remplissent la même condition permettant à certaines relations d’être reconnues comme des relations de sollicitude, mais que des injustices épistémiques restreignent leur reconnaissance en tant que relations de sollicitude. Enfin, j’analyse, au sein du troisième chapitre, les différentes pistes de solution aux injustices épistémiques et institutionnelles subies par les personnes au sein de relations de sollicitude marginalisées afin d’identifier lesquelles seraient le mieux en mesure de contribuer au démantèlement de ces injustices. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : relations interpersonnelles, relations de sollicitude, justice sociale, injustice épistémique, communauté LGBTQIA2S+, amatonormativité, cishétéronormativité, enjeux de reconnaissance
Keywords: LGBTQIA2+; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; patriarcat; philosophie; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Hermeneutical Backlash: Trans Youth Panics as Epistemic Injustice - George, B. R.; Goguen, Stacey (Feminist Philosophy Quarterly, 2021)
In this paper we use the contemporary example of trans youth panics to introduce the notion of hermeneutical backlash, in which defenders of an established, unjust hermeneutical regime actively work to undermine and discredit hermeneutical liberation. We argue that the strategies and tropes of the trans youth panic illustrate a general propaganda vulnerability of epistemic liberation movements (including familiar examples from recent history), and so are troubling for reasons that go beyond their application to trans youth. This exploration of a few specific cases of hermeneutical liberation and hermeneutical backlash calls attention to the need for further theoretical work on the dynamics of struggles for (and against) hermeneutical justice.
Keywords: approches et analyses; backlash herméneutique; cours; cycles supérieurs; discipline; discours dominant; discours médiatique; enfants trans*; fem9000; histoire et politique; hétérosexisme; injustices herméneutiques; militance; philosophie; philosophie féministe; sciences humaines; systèmes d'oppressions; thématiques; transphobie; violences

Beyond Binary: Genderqueer as Critical Gender Kind - Dembroff, Robin (Philosophers' Imprint, 2020)
We want to know what gender is. But metaphysical approaches to this question solely have focused on the binary gender kinds men and women. By overlooking those who identify outside of the binary–the group I call ‘genderqueer’–we are left without tools for understanding these new and quickly growing gender identifications. This metaphysical gap in turn creates a conceptual lacuna that contributes to systematic misunderstanding of genderqueer persons. In this paper, I argue that to better understand genderqueer identities, we must recognize a new type of gender kind: critical gender kinds, or kinds whose members collectively destabilize one or more pieces of dominant gender ideology. After developing a model of critical gender kinds, I suggest that genderqueer is best modeled as a critical gender kind that destabilizes the ‘binary axis’, or the piece of dominant gender ideology that says that the only possible genders are the binary, discrete, exclusive, and exhaustive kinds men and women.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; hétérosexisme; identités LGBTQIA2+; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sofia; systèmes d'oppressions; thématiques; états-unis

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge studies in contemporary philosophy, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"-- Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap